Multidisciplinary Approaches to Cardiac Risk Management Synergy between Nurses, ECG Technicians, and Pharmacists - Aldhuwaila, Adel Sulaiman; Sulobi Alharbi, Abdullatif; Saad Alsulihem, Sama; Salem AL Bishi, Eman; Eshaiwi alenazi, Maha; Mudhhi Alanazi, Abdulelah; Almutairi, Amal Saleem; Abbad Alotaibi, Faisal (Journal of Neonatal Surgery, 2025)
The CVDs are the most common cause of death globally and cause strain on the healthcare system Respiratory CVDs complicate the healthcare system due to rising risks factors in the population such as hypertension and diabetes. Effective management of cardiac and related diseases is needed. This explains the importance of multidisciplinary care involving nursing, ECG techs and pharmacists. Nursing, as education and monitoring of patients, leads in lifestyle changes, control of the symptoms, and adherence to effective medications. ECG Techs also play an important role in diagnosing and detecting cardiac conditions that are potentially very invasive. Ischemia and other arrhythmias are detected by ECG testing, allowing intervention. While pharmacists also play an important role in medication management by monitoring, optimizing adherence, and detecting potential interactions. Providing multidisciplinary care has been shown to improve outcomes. Communication challenges, role overlaps, and resource gaps have been shown to impact effective multidisciplinary care. Addressing these barriers has been shown to improve communication, training gaps, and healthcare team integration. This is a review of the role multidisciplinary care contributes and the importance of the integration for the provision of nursing care and ECG tech/pharmacist care. Systemic challenges can be overcome through collaboration in healthcare systems to improve CVD management and reduce the burden they cause globally